“Understanding the Architecture of Human Thought”? Questioning the Mathematical Conception of Nature with Heidegger - Williams, Anita (Investigaciones Fenomenológicas, 2021)
New technologies, such as functional magnetic resonance imaging (fMRI) and transcranial magnetic stimulation (TMS), are currently touted as, not only giving us a better picture of the structure of the brain, but also a better understanding of our thinking. As Alan Snyder demonstrates when he claims his aim is to understand the ‘architecture of thought’ by investigating the brain. Against this backdrop, I will argue that new technologies present a worrying extension of mathematical natural science into the domain of human affairs. Extrapolating upon Heidegger, I will put forward that neuroscientific experiments force thinking to conform to the mathematical conception of nature, rather than reveal something about the ‘true’ nature of our thinking. In a time when the expansion of mathematical natural science threatens to reduce every domain to that which is quantifiable, I will conclude by suggesting that the responsibility of the philosopher is to question the presuppositions of modern science and psychology. Nuevas tecnologías como la imagen de resonancia magnética funcional (fMRI) y la estimulación magnética transcranial se consideran presumiblemente capaces de darnos no solo una mejor imagen de nuestro cerebro, sino también una mejor comprensión de nuestro pensamiento, tal como demuestra Alan Snyder cuando afirma que su objetivo es entender la “arquitectura del pensamiento” mediante la investigación del cerebro. Contra este marco general, argumentaré que las nuevas tecnologías nos presentan una preocupante extensión de la ciencia natural matemática al dominio de los asuntos humanos. Extrapolando a partir de Heidegger, propondré que los experimentos neurocientíficos fuerzan al pensamiento a conformarse a la concepción matemática de la naturaleza en vez de revelar algo sobre la verdadera naturaleza de nuestro pensamiento. Nos encontramos en un momento en que o la expansión de la ciencia natural matemática amenaza con reducir todos los dominios a lo que es cuantificable. Concluiré sugiriendo que la responsabilidad del filósofo es cuestionar los presupuestos de la ciencia moderna y de la psicología.